Reforming scholarly publishing and knowledge communication - Correia, Ana Maria Ramalho (2019)
Correia, A. M. R., & Teixeira, J. C. (2005). Reforming scholarly publishing and knowledge communication: From the advent of the scholarly journal to the challenges of open access. Online Information Review, 29(4), 349-364. https://doi.org/10.1108/14684520510617802